2015
DOI: 10.1039/c5ra01911g
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid: a versatile antioxidant with promising therapeutic and industrial applications

Abstract: Oxidative stress, a result of an overproduction and accumulation of free radicals, is the leading cause of several degenerative diseases such as cancer, atherosclerosis, cardiovascular diseases, ageing and inflammatory diseases. Polyphenols form an important class of naturally occurring antioxidants, having innumerable biological activities such as anticancer, antifungal, antibacterial, antiviral, antiulcer and anticholesterol, to name a few. Among various polyphenols, gallic acid (3,4,5-trihydroxybenzoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
548
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 864 publications
(577 citation statements)
references
References 281 publications
(437 reference statements)
19
548
0
10
Order By: Relevance
“…Peels of pomegranate, lemon, orange, and apple are the major sources of vitamins C and A, 10 whereas pomegranate peels contain antioxidants, especially polyphenols. 41,42 Using fruit waste as a cheaper bioreductant is a fascinating, simple, and green approach.…”
Section: Biosynthesis and Characterization Of Spionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peels of pomegranate, lemon, orange, and apple are the major sources of vitamins C and A, 10 whereas pomegranate peels contain antioxidants, especially polyphenols. 41,42 Using fruit waste as a cheaper bioreductant is a fascinating, simple, and green approach.…”
Section: Biosynthesis and Characterization Of Spionsmentioning
confidence: 99%
“…Broad absorbance peak may likely result from various capping agents coming from different natural compounds. 10,27,29,42,45 The proceeding reaction could be envisioned via color changes in the resulting colloidal solution. Phytochemicals bound to the surface of bio-SPIONs are rich in hydrophilic hydroxyl groups that allowed the NPs to disperse and distribute homogenously in aqueous media (Table S1).…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…GA forms a free radical at the C4 hydroxyl position which is stabilized by the two adjacent AOH groups via intramolecular hydrogen bonding. [79] This ease of formation of free radicals and subsequent stabilization makes GA an essential candidate for prevention of oxidative stress. Our experiment showed that the other two polyphenols (ECG and EGCG) possess greater antioxidant activity over GA both in the free and encapsulated state.…”
Section: Docking Studiesmentioning
confidence: 99%
“…HE protective action of polyphenols is well known, [1][2][3][4][5] but the mode of their action has not yet been sufficiently explained. There are general reaction mechanisms for scavenging of radicals by polyphenols, such as single-step hydrogen atoms transfer (HAT), single electron transfer followed by proton transfer (SET-PT) and sequential proton loss electron transfer (SPLET).…”
Section: Introductionmentioning
confidence: 99%